The Effect of Liquid Organic Fertilizer Made from Eggshells and Sugarcane Bagasse on the Growth of Cayenne Pepper - Nasution, Zulfikar; Dini Hariyati Adam; Khairul Rizal; Yudi Triyanto (Jurnal Ekonomi, 2024)
Indonesia is an agricultural country. Indonesia's soil structure is fertile and has a tropical climate. Cayenne pepper is a horticultural crop cultivated by farmers. Cayenne pepper production fluctuates from year to year. The leading cause of the lack of cayenne pepper production is land. Efforts are needed to increase production, one of which is intensifying fertilization. One of the liquid organic fertilizers is organic fertilizer from eggshells. Egg shells can be used as an organic fertilizer because they contain nutrients such as calcium carbonate, nitrogen, potassium, and phosphorus. One alternative provider of nutrients for plants is sugar cane bagasse. Sugarcane bagasse contains the elements Carbon (C), Nitrogen (N, Phosphate (P), Potassium (K), Sodium (Na), Calcium (Ca), Magnesium (Mg), Iron (Fe), and Manganese (Mn). Research This study aims to see the effect of liquid organic fertilizer made from egg shells and sugar cane bagasse on the growth of cayenne pepper. This research also aims to study and determine the effect of applying liquid organic fertilizer made from egg shells and sugar cane bagasse on the growth of cayenne pepper. Liquid made from egg shells and bagasse is the best for the growth of cayenne pepper. Research shows that treating liquid organic fertilizer with egg shells and bagasse affects the weight, length, weight per plot, and number of cayenne peppers planted. However, it does not significantly affect the lifespan of cayenne pepper flowers. An 80% concentration treatment of liquid organic fertilizer from egg shells and bagasse showed the best results.